2020
DOI: 10.32479/ijeep.8389
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Environmental Kuznet Curve and Urban Environment Transition Hypotheses in Malaysia

Abstract: The aim of this paper is to examine the interconnection bewteen the environmental Kuznet curve (EKC) and urban environment transition hypotheses in the Malaysian economy. Economic growth, CO 2 emissions, energy consumption, financial development (FD), urbanization variables for the 1971-2013 period, F-bound tests, and multivariate Granger causality methods are used. The long-run relationships among the above series of variables are examined. Also, the findings confirm the existence of an inveretd EKC hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 109 publications
2
9
0
Order By: Relevance
“…This result could be attributed to Grossman and Krueger (1991), where they found a non-linear relation between CO 2 emissions and economic growth, which is an inverted U-shaped relationship. Also, this result is consistent with Suki et al (2020) and Bekhet et al (2020).…”
Section: Results Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…This result could be attributed to Grossman and Krueger (1991), where they found a non-linear relation between CO 2 emissions and economic growth, which is an inverted U-shaped relationship. Also, this result is consistent with Suki et al (2020) and Bekhet et al (2020).…”
Section: Results Analysissupporting
confidence: 90%
“…Many studies investigated the relationship between GDP and environmental pollution. For example, Bekhet et al (2020), Begum et al (2015), Al-Mulali et al (2015), Ozturk and Al-Mulali (2015) investigate the trade-off between carbon dioxide emissions and GDP in the Environmental Kuznets Curve (EKC) framework. Other studies investigated the role of urbanization in determining the interaction between carbon emission and GDP (Sadorsky, 2014;Martinez-Zarzosa and Maruotti, 2011;He et al, 2017;Ozturk and Al-Mulali, 2015;Bekhet and Othman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bekhet and Othman (2017) explored the linkage among urbanization, energy consumption, economic growth, and financial development and CO 2 emissions in Malaysia and found that urbanization can have a significant impact on CO 2 emissions with two different stages. Bekhet et al (2020) extended the study by reinvestigating the interaction between the environmental Kuznets curve and urban environment transition hypotheses in Malaysia. The results showed that urbanization can have a negative impact on the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kuznets Curve Environmental Theory states that cases in developing countries over time, technological advances can damage natural and environmental sustainability [3]. Meanwhile, in developed countries over time technological advances can improve environmental sustainability [14]. This theory is known as the first theory to describe how the relationship between economic growth rates and environmental degradation [3].…”
Section: Introductionmentioning
confidence: 99%